Determinants of stunting during the first 1, 000 days of life in Bangladesh: A review. Issue 9 (20th July 2020) - Islam, Md Shariful; Zafar Ullah, Abu Naser; Mainali, Shristi; Imam, Md. Akhter; Hasan, Md Imran
Abstract: Stunting is a major problem in Bangladesh, with a prevalence of 31% in 2017. The prevalence of stunting in children aged under two has reduced by only 6% since 2004. After children reach 2 years of age, the consequences of stunting become almost irreversible. This paper seeks to examine and analyze the determinants associated with stunting during the first 1, 000 days of life in Bangladesh to assist in developing evidence‐based interventions in Bangladesh. A literature review was conducted comprehensively on all relevant peer‐reviewed and gray literature of studies conducted in Bangladesh. The existing literature was searched and examined using the World Health Organization (WHO) conceptual framework for stunting. Evidence indicates that low maternal weight, lack of maternal education, severe food insecurity, lack of access to suitable nutrition, nonexclusive breastfeeding, pathogen‐specific diarrhea, and low weight and height at birth are associated with early childhood stunting in Bangladesh. The relation of the quality of drinking water with stunting is not clear in Bangladesh. Literature about the association between stunting and determinants such as the political economy, education systems, and agriculture and food systems is not found. This synthesis shows that the factors of stunting are multifaceted. As such, a multi‐sectoral approach is essential in Bangladesh, employing evidence‐based interventions to address the determinants that contribute to the risk of stunting to achieve the global nutrition target by 2025. Abstract : Stunting is a major problem in Bangladesh, with a prevalence of 31% in 2017. Evidence shows that low maternal weight, lack of maternal education, severe food insecurity, lack of access to adequate nutrition, nonexclusive breastfeeding, pathogen‐specific diarrhea, and low weight and height at birth are correlated with early childhood stunting in Bangladesh. In Bangladesh, current studies are ambiguous about whether drinking water quality is correlated with stunting.